(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Right to life, which is described underArticle 21 of the Constitution also aids in giving citizens a right to live alife of dignity. A life with full control over it is supposedly guaranteed bythe constitution. The conflict, however, begins here. Liberty is guaranteed toan individual but no such right is given to end his life with his own will.This debate has been the subject is cases of P. Rathinam v. Union of India andSmt. Gian Kaur v. State of Punjab. In P. Rathinam, the Supreme Court held theright to die as an aspect of article 21. It was held that the section 309 wasviolative of article 21 of theconstitution inasmuch as right to live includes right to die or right not tolive a forced life and the section interferes with that right. The court agreedwith the reasoning given by Bombay High Court in the case of Maruti Shripati Dubai v. State of Maharashtra, “ thefreedom of speech and expression includes freedom not to speak and to remainsilent. The freedom of association and Movement likewise includes the freedomnot to join any association or to move anywhere. The freedom of business andoccupation includes freedom not to do business and to close down the existingbusiness. If this is so, logically it must follow that right to live asrecognized by Article 21 of the constitution will include also a right not tolive or not to be forced to live . To put it positively, Article 21 wouldinclude a right to die, or to terminate one’s life”